(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
Annotation. The purpose and content of education allows to choose the right methods. Whatever the goal, the methods of achieving it must be in accordance with it. The content of education consists of the essence of social requirements for the formation of a person. Do not forget that the same task can be filled with different ideas. Therefore, it is very important to connect the methods not with the content in general, but with a specific idea. Age characteristics of students. In the process of education, it is appropriate to take into account the young characteristics of the students. Age characteristics are anatomical, physiological and psychological characteristics characteristic of a certain age period